Secondhand souls [compact disc, unabridged] - Moore, Christopher, 1957- (Harper Audio, 2015)
Something really strange is happening in the City by the Bay. People are dying, but their souls are not being collected. Someone-or something-is stealing them and no one knows where they are going, or why, but it has something to do with that big orange bridge. Death Merchant Charlie Asher is just as flummoxed as everyone else. He's trapped in the body of a fourteen-inch-tall "meat puppet" waiting for his Buddhist nun girlfriend, Audrey, to find him a suitable new body to play host.